Localisation of a gene for transient neonatal diabetes mellitus to an 18.72 cR3000 (∼5.4 Mb) interval on chromosome 6q. Issue 3 (1st March 1999) - Gardner, Rebecca J; Mungall, Andrew J; Dunham, Ian; Barber, John C K; Shield, Julian P H; Temple, I Karen; Robinson, David O
Abstract : Transient neonatal diabetes mellitus (TNDM) is a rare condition which presents with intrauterine growth retardation, dehydration, and failure to thrive. The condition spontaneously resolves before 1 year of age but predisposes patients to type 2 diabetes later in life. We have previously shown that, in some cases, TNDM is associated with paternal uniparental disomy (UPD) of chromosome 6 and suggested that an imprinted gene responsible for TNDM lies within a region of chromosome 6q. By analysing three families, two with duplications (family A and patient C) and one with several affected subjects with normal karyotypes (family B), we have further defined the TNDM critical region. In patient A, polymorphic microsatellite repeat analysis identified a duplicated region of chromosome 6, flanked by markers D6S472 and D6S311. This region was identified on the Sanger Centre's chromosome 6 radiation hybrid map (http://www.sanger.ac.uk/HGP/Chr6 ) and spanned approximately 60 cR3000 . Using markers within the region, 418 unique P1 derived artificial chromosomes (PACs) have been isolated and used to localise the distal breakpoints of the two duplications. Linkage analysis of the familial case with a normal karyotype identified a recombination within the critical region. This recombination has been identified on the radiation hybrid map and defines the proximal end of the region of interest. We therefore propose that an imprinted gene for TNDM lies within an 18.72 cR3000 (∼5.4 Mb) interval on chromosome 6q24.1-q24.3 between markers D6S1699 and D6S1010.